2016
DOI: 10.1016/j.jconrel.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional exosome-mimic for delivery of siRNA to cancer: in vitro and in vivo evaluation

Abstract: Exosomes, the smallest subgroup of extracellular vesicles, have been recognized as extracellular organelles that contain genetic and proteomic information for long distance intercellular communication. Exosome-based drug delivery is currently a subject of intensive research. Here, we report a novel strategy to produce nanoscale exosome-mimics (EMs) in sufficient quantity for gene delivery in cancer both in vitro and in vivo. Size-controllable EMs were generated at a high yield by serial extrusion of non-tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(135 citation statements)
references
References 35 publications
(31 reference statements)
2
123
0
Order By: Relevance
“…Paduano et al (23) revealed that si-survivins markedly reduced the expression level of survivin and produced supra-additive growth suppression in human androgen-independent prostate cancer cells. Numerous previous studies have directly added siRNA mimics into cell cultures (3537). However, the major limitations of direct addition of siRNA mimics to cells are the instability and short half-life time.…”
Section: Discussionmentioning
confidence: 99%
“…Paduano et al (23) revealed that si-survivins markedly reduced the expression level of survivin and produced supra-additive growth suppression in human androgen-independent prostate cancer cells. Numerous previous studies have directly added siRNA mimics into cell cultures (3537). However, the major limitations of direct addition of siRNA mimics to cells are the instability and short half-life time.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase (CK), isocitric dehydrogenase (ICDH), and hydroxybutyrate dehydrogenase (HBDH) in rat serum were determined by detection kits according to the instructions that were provided by Changzheng Biochemical Reagent Co, Ltd, Shanghai, China. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Though no control comparison was made to native EVs derived from the same β-cell line, a yield of 8.2 × 10 8 particles per 1 µg of total protein was reported, confirming that generally a high number of vesicles can be made from this method [105]. A similar protocol was used to produce EV mimics from human breast epithelial cells [106]. A significantly higher yield of mimics was seen, with 379.3 µg of protein and 3.0 × 10 11 of mimics produced in comparison to 2.5 µg of protein and 2.6 × 10 9 of EVs from the same number of cells (1.0 × 10 7 cells).…”
Section: Cell-derived Nanovesiclesmentioning
confidence: 99%